EFEKTIFITAS FUNGI MIKORIZA ARBUSKULA DAN PLANT GROWTH PROMOTING BACTERIA TERHADAP PERTUMBUHAN Aquillaria crassna - Ragil S.B Irianto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2015)
Aquilaria crassna is an exotic plant producing agarwood. This research aimed to observe arbuscular mychorrhizal fungi (AMF) and plant growth promoting rhizobacteria (PGPR) effectiveness on growth of A. crassna in nursery and field. Experiments were arranged in a randomized completed blockdesign in the field. Seedlings were inoculated with Glomus ACA, Glomus SWM, PGPR, Glomous ACA+PGPR, and uninoculated seedlings as a control. Result showed that inoculation with Glomus ACA, Glomus SWM, dan PGPR could accelerated height and diameter of 8-months-old seedling significantly as much as 127, 128, 94; dan 51, 52, 39% compared to control. Inoculation Glomus ACA, Glomus SWM, still could be accelerated plant growth of height and diameter of 6-months-old young trees as much as 67.81% and 66.7% compared to control.